The genomic landscape of diffuse intrinsic pontine glioma and pediatric non-brainstem high-grade glioma - Wu, Gang; Diaz, Alexander K; Paugh, Barbara S; Rankin, Sherri L; Ju, Bensheng; Li, Yongjin; Zhu, Xiaoyan; Qu, Chunxu; Chen, Xiang; Zhang, Junyuan; Easton, John; Edmonson, Michael; et al. (Nature genetics, 2014)
Suzanne Baker, Jinghui Zhang and colleagues report the identification of recurrent somatic mutations in the bone morphogenetic protein (BMP) receptor ACVR1 in 32% of diffuse intrinsic pontine gliomas. Pediatric high-grade glioma (HGG) is a devastating disease with a less than 20% survival rate 2 years after diagnosis 1 . We analyzed 127 pediatric HGGs, including diffuse intrinsic pontine gliomas (DIPGs) and non-brainstem HGGs (NBS-HGGs), by whole-genome, whole-exome and/or transcriptome sequencing. We identified recurrent somatic mutations in ACVR1 exclusively in DIPGs (32%), in addition to previously reported frequent somatic mutations in histone H3 genes, TP53 and ATRX , in both DIPGs and NBS-HGGs 2 , 3 , 4 , 5 . Structural variants generating fusion genes were found in 47% of DIPGs and NBS-HGGs, with recurrent fusions involving the neurotrophin receptor genes NTRK1, NTRK2 and NTRK3 in 40% of NBS-HGGs in infants. Mutations targeting receptor tyrosine kinase–RAS-PI3K signaling, histone modification or chromatin remodeling, and cell cycle regulation were found in 68%, 73% and 59% of pediatric HGGs, respectively, including in DIPGs and NBS-HGGs. This comprehensive analysis provides insights into the unique and shared pathways driving pediatric HGG within and outside the brainstem.